Advances in Selective Flotation and Leaching Process in Metallurgy - Park, Ilhwan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Metals are necessary to maintaining living standards in modern society, due to their countless applications in transportation, building and construction, household appliances, electronic devices, etc. Therefore, humans' generation and consumption of metals is considerable, and demand is projected to skyrocket continuously as technology advances. Unfortunately, easily exploitable ore deposits have been depleted, which forces mining industries to develop complex ore deposits with low-grade and fine grain sizes to meet the high forecasted demand for metals. In general, metals can be extracted from ores in two ways; either by the concentration of valuable minerals via flotation followed by smelting, or by direct extraction of metals from ores via leaching followed by purification and recovery processes. The first stages in each scenario, flotation and leaching are, therefore, of crucial importance to ensuring the continued supply of metals. This book is a compilation of a Special Issue of Metals, entitled "Advances in Selective Flotation and Leaching Process in Metallurgy", where 12 papers contributed by experts in the area were published. Papers published in this Special Issue cover a wide range of topics, including flotation, microencapsulation, agglomeration, leaching, solvent extraction, electrowinning, precipitation, and cementation. All the papers are of high scientific value and will be of great interest to the readers of Metals.